Pleuro-peritoneal or pericardio-peritoneal leak in children on chronic peritoneal dialysis-A survey from the European Paediatric Dialysis Working Group - Dufek, Stephanie; Holtta, Tuula; Fischbach, Michel; Ariceta, Gema; Jankauskiene, Augustina; Cerkauskiene, Rimante; Schmitt, Claus Peter; Schaefer, Betti; Aufricht, Christoph; Wright, Elizabeth; Stefanidis, Constantinos J; Ekim, Mesiha; et al. (Pediatric nephrology (Berlin, Germany), 2015)
BACKGROUND: Pleural or pericardial effusions secondary to pleuro-peritoneal fistula (PPF) and pericardio-peritoneal fistula (PcPF) are rare but serious complications of peritoneal dialysis (PD). METHODS: We conducted a 10-year survey across all participating centres in the European Paediatric Dialysis Working Group to review the incidence, diagnostic techniques, therapeutic options and outcome of children on chronic PD with PPF and/or PcPF. RESULTS: Of 1506 children on PD there were ten cases (8 of PPF, 1 each of PcPF and PPF + PcPF), with a prevalence of 0.66%. The median age at presentation was 1.5 [inter-quartile range (IQR) 0.4-2.4] years, and nine children were <3 years. The time on PD before onset of symptoms was 4.3 (IQR 1.3-19.8) months. Eight children had herniae and seven had abdominal surgery in the preceding 4 weeks. Symptoms at presentation were respiratory distress, reduced ultrafiltration and tachycardia. PD was stopped in all children; three were managed conservatively and thoracocentesis was performed in seven (with pleurodesis in 3). PD was restarted in only three children, in two of them with success. CONCLUSION: In conclusion, PPF and PcPF are rare in children on chronic PD, but are associated with significant morbidity, requiring a change of dialysis modality in all cases. Risk factors for PPF development include age of <3 years, herniae and recent abdominal surgery.
Keywords: perikardiální efuze; Surveys and Questionnaires; Kidney Failure, Chronic; Infant; Humans; Pericardial effusion; kojenec; dítě; prevalence; Child; ascitická tekutina; Female; peritoneální dialýza; lidé; Europe; Children; Pleural Effusion; Pleuro-peritoneal fistula; Pericardio-peritoneal fistula; průzkumy a dotazníky; Pleural effusion; předškolní dítě; Peritoneal Dialysis; Fistula; ženské pohlaví; chronické selhání ledvin; pleurální výpotek; Male; Pericardial Effusion; incidence; píštěle; Incidence; Prevalence; mužské pohlaví; Child, Preschool; Peritoneal dialysis; Ascitic Fluid; Evropa